Pengaruh Kepemimpinan dan Manajemen Pengetahuan terhadap Kinerja Pegawai PT Bank Syariah Indonesia Kantor Regional Aceh - Muhammad Nugraha Argiandista; Erlinda Erlinda; Yuslaidar Yusuf (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
Bank Syariah Indonesia (BSI), the result of a merger of three state-owned Islamic banks, strengthens the national and global Islamic banking industry, but the quality of human resources remains a challenge because most employees do not have a background in Islamic economics. Employee performance is influenced by leadership and knowledge management, which combines motivation, information management, effective communication, creative innovation, team collaboration, and strategic decision-making that supports productivity. This condition emphasizes the importance of research on the influence of leadership and knowledge management on employee performance at Bank Syariah Indonesia (BSI) Aceh Regional Office to support BSI's vision as a modern, professional, innovative, inclusive, and globally competitive Islamic bank. This study aims to examine and analyze the influence of leadership and knowledge management on the performance of employees at Bank Syariah Indonesia (BSI) Aceh Regional Office. In this study, the population consists of all 76 employees at Bank Syariah Indonesia (BSI) Aceh Regional Office. Sampling was conducted using the census technique, whereby the entire population was used as the sample. The data analysis method used was multiple linear regression analysis. The results of the study indicate that leadership partially influences the performance of employees at Bank Syariah Indonesia (BSI) Aceh Regional Office. Knowledge management partially influences the performance of employees at Bank Syariah Indonesia (BSI) Aceh Regional Office. Leadership and knowledge management simultaneously have a significant influence on the performance of employees at Bank Syariah Indonesia (BSI) Aceh Regional Office.